2021
DOI: 10.3390/cells10102619
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bile Acid Metabolism and Gut Dysbiosis in Mice Lacking Lysosomal Acid Lipase

Abstract: Lysosomal acid lipase (LAL) is the sole enzyme known to be responsible for the hydrolysis of cholesteryl esters and triglycerides at an acidic pH in lysosomes, resulting in the release of unesterified cholesterol and free fatty acids. However, the role of LAL in diet-induced adaptations is largely unexplored. In this study, we demonstrate that feeding a Western-type diet to Lal-deficient (LAL-KO) mice triggers metabolic reprogramming that modulates gut-liver cholesterol homeostasis. Induction of ileal fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
(111 reference statements)
4
3
0
Order By: Relevance
“…The increased number of immune cells, especially macrophages, in various organs such as liver, lung or SI of LAL KO mice already suggested that they play a crucial role in the pathogenesis of LAL-D [ 32 ]. Our present findings demonstrate that infiltrating macrophages are responsible for the severe lipid accumulation in LAL KO mice, predominantly incorporating lipids from the circulation, as recently suggested [ 31 ]. We have identified a macrophage subclass that is very similar to LAMs and DAM and whose most prominent marker is TREM2 [ 43 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The increased number of immune cells, especially macrophages, in various organs such as liver, lung or SI of LAL KO mice already suggested that they play a crucial role in the pathogenesis of LAL-D [ 32 ]. Our present findings demonstrate that infiltrating macrophages are responsible for the severe lipid accumulation in LAL KO mice, predominantly incorporating lipids from the circulation, as recently suggested [ 31 ]. We have identified a macrophage subclass that is very similar to LAMs and DAM and whose most prominent marker is TREM2 [ 43 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Since macrophages of the lamina propria are located in close proximity to blood vessels, lipids taken up from the basolateral side (circulation) are more likely to contribute to the formation of lipid-filled macrophages than dietary lipids. Consistent with our data from chow diet-fed LAL KO mice, LAL KO mice fed a Western-type diet had increased basolateral lipid uptake, which was associated with impaired dietary lipid absorption and higher fecal lipid loss [ 31 ]. Lipid-filled macrophages are mainly present in the duodenum of LAL KO mice, which is in agreement with the fact that basolateral lipid uptake is more pronounced in the proximal part of the SI and gradually decreases in the jejunum and ileum [ 23 , 31 , 52 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of the most affected tissues in patients suffering from LAL deficiency (LAL-D) is the SI, in which massive lipid accumulation causes gastrointestinal symptoms, such as vomiting, diarrhea with steatorrhea, and abdominal distension . We and others have shown that the SI of Lal-deficient (KO) mice is severely affected due to pronounced macrophage infiltration. Interestingly, we observed that macrophages, not enterocytes, are the main cell type that accumulated lipids in these mice, suggesting that LAL does not play a crucial role in lipid metabolism in enterocytes . The infiltrating macrophages in the duodenum of Lal KO mice displayed a triggering receptor expressed on myeloid cells-2 (Trem2)-like gene signature previously identified in lipid-associated macrophages (LAMs) and disease-associated macrophages …”
Section: Introductionmentioning
confidence: 78%
“…LAL is present in all cell types with the exception of erythrocytes ( Grabowski et al, 2019 ), and participates in multiple physiological processes in different tissues. Additional roles for LAL have been elucidated in thermogenesis ( Duta-Mare et al, 2018 ; Fischer et al, 2021 ; Fischer et al, 2022 ), bile acid metabolism with effects on the gut microbiome ( Sachdev et al, 2021 ), insulin sensitivity ( Radović et al, 2016 ), and retinoic acid metabolism ( Grumet et al, 2016 ).…”
Section: Lipa /Lal Regulation and Functionmentioning
confidence: 99%